Alpine Strawberry as a Potential Niche Crop for Florida Growers and Homeowners - Alan H Chambers (EDIS)
Alpine strawberries (Fragaria vesca) produce edible and highly aromatic strawberries known for their excellent eating quality. The berries are fragile and not suitable for long-distance shipping, which inhibits trade on the international market but also provides an opportunity for growers catering to local markets and for homeowners interested in growing this unique and delicious strawberry. This 5-page fact sheet written by Alan Chambers and published by the UF/IFAS Horticultural Sciences Department describes yield and fruit quality for several varieties to guide potential growers. The results of this project are anticipated to benefit growers and homeowners looking to cultivate specialty alpine strawberries. http://edis.ifas.ufl.edu/hs1326